1998
DOI: 10.1074/jbc.273.27.16798
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Conserved Erythroid-specific Enhancer Located in Intron 8 of the Human 5-Aminolevulinate Synthase 2 Gene

Abstract: Thirty five kilobases of sequence encompassing the human erythroid 5-aminolevulinate synthase (ALAS2) gene have been determined. Analysis revealed a very low GC content, few repetitive elements, and evidence for the insertion of a reverse-transcribed mRNA sequence and a neighboring gene. We have investigated whether introns 1, 3, and 8, which correspond to DNase I-hypersensitivity sites in the structurally related mouse ALAS2 gene, affect expression of the human ALAS2 promoter in transient expression assays. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 68 publications
4
59
0
Order By: Relevance
“…5E). Exogenous reporter assays have shown that, depending on the exact "chunks" of DNA tested, this region can vary in activation strength and even repress (51). Intriguingly, when we separately targeted two GATA1 motifs in ALAS2 intron 8 with CRISPR/Cas9, we observed an increase in ALAS2 mRNA expression, similar to the results obtained by targeting two CREs near SLC4A1, suggesting that these regions may have a particularly complex regulatory architecture (Fig.…”
Section: Understanding and Predicting The Effects Of Nc Mutations On supporting
confidence: 73%
See 1 more Smart Citation
“…5E). Exogenous reporter assays have shown that, depending on the exact "chunks" of DNA tested, this region can vary in activation strength and even repress (51). Intriguingly, when we separately targeted two GATA1 motifs in ALAS2 intron 8 with CRISPR/Cas9, we observed an increase in ALAS2 mRNA expression, similar to the results obtained by targeting two CREs near SLC4A1, suggesting that these regions may have a particularly complex regulatory architecture (Fig.…”
Section: Understanding and Predicting The Effects Of Nc Mutations On supporting
confidence: 73%
“…Intriguingly, when we separately targeted two GATA1 motifs in ALAS2 intron 8 with CRISPR/Cas9, we observed an increase in ALAS2 mRNA expression, similar to the results obtained by targeting two CREs near SLC4A1, suggesting that these regions may have a particularly complex regulatory architecture (Fig. S9) (51). Taken together, our analyses provide additional evidence that erythroid CREs are dependent on the binding of multiple TFs for proper transcriptional regulation and RBC development.…”
Section: Understanding and Predicting The Effects Of Nc Mutations On supporting
confidence: 68%
“…To establish whether differential chromatin access underlies the distinct sensitivities, the ER-GATA-1 level͞activity was titrated with 5, 10, or 40 nM ␤-estradiol for 16 h, and chromatin occupancy was measured at sites defined previously (13,14,20,22,28,(43)(44)(45). ER-GATA-1 occupied ␤-globin HSs1-4 maximally and the ␤major promoter nearly maximally in 10 nM ␤-estradiol-treated cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, sptb (39) and alas2 (40)(41)(42) genes have been shown to have GATA binding sites within their promoters that are required for transactivation in tissue culture. In the zebrafish, embryonic globin gene expression was observed earlier (at 3-6 somites) than sptb, alas2, and band3 (at 16 somites) (S.E.L., unpublished results).…”
Section: Discussionmentioning
confidence: 99%